Investigating the accuracy of ultrasound viscoelastic creep imaging for measuring the viscoelastic properties of a single-inclusion phantom. (1st June 2021) - Lin, Che-Yu; Lin, Siang-Rong
Highlights: Ultrasound viscoelastic creep imaging could be difficult to accurately measure the viscoelastic properties of the inclusion within a single-inclusion phantom. Ultrasound viscoelastic creep imaging could accurately measure the viscoelastic properties of the background material within a single-inclusion phantom. The application value and usefulness of ultrasound viscoelastic creep imaging in clinical and biomedical applications on biological tissues and biomaterials could be limited and doubtful. Further research on the design of ultrasound viscoelastic creep imaging is necessary to overcome the current limitations and realize its value and usefulness in applications. Abstract: Ultrasound viscoelastic creep imaging is a noninvasive technique that has potential to measure the internal spatial distribution of viscoelastic properties of materials, based on inducing the creep response of the material and using a viscoelastic mechanical model to analyze the creep response. Since how viscoelastic creep imaging can be applied to accurately measure the viscoelastic properties of heterogeneous materials is still unclear, the purpose of this study is to use finite element computer simulation to quantitatively investigate the accuracy of compressional viscoelastography (viscoelastic creep imaging using external mechanical compression as the source of excitation) on measuring the viscoelastic properties of a single-inclusion phantom. The study intends to answer a question: can compressional viscoelastography accurately measure the viscoelastic properties of the inclusion as well as the background material within a single-inclusion phantom? Based on the simulation results, compressional viscoelastography could not accurately measure the viscoelastic properties of the inclusion. The measurement of a viscoelastic property (modulus of elasticity or relaxation time constant) of the inclusion is accurate if and only if the difference in that property between the inclusion and background material is very small, less than around 10%. On the other hand, compressional viscoelastography can accurately measure the viscoelastic properties of the background material regardless of the difference in the viscoelastic properties between the inclusion and background material. In a real biological tissue, the mechanical behaviors are much more complicated and unpredictable than those in a single-inclusion phantom like the one used in the present study. Hence, based on the simulation results of the present study, it could be more challenging to apply compressional viscoelastography to accurately measure the viscoelastic properties of a mass or a target tissue within a real biological tissue. The findings of the present study based on compressional viscoelastography may also be applicable to acoustic-radiation-force-based viscoelastic creep imaging. In the future, experiments are needed to justify the simulation results found in the present study. Graphical abstract: Image, graphical abstract